INDONESIAN BANKRUPTCY LAW POLICY AFTER POLITICAL & MONETARY TURMOIL IN 1998 - Gede Aditya Pratama; Elfirda Ade Putri; Arga Pribadi Imawan (JURNAL ILMU SOSIAL, 2024)
The monetary turmoil that occurred in 1998 plunged Indonesia into an economic crisis that had an unfavorable impact on the national economy, which at the time was dependent on foreign investment. In the end, to help improve the economy in Indonesia, the Government at that time took action to ask for assistance from the International Monetary Fund (IMF). The injection of funds from the International Monetary Fund (IMF) provided conditions for the Government of Indonesia to establish new bankruptcy regulations from the commonly used Dutch Bankruptcy Law of 1905 (Faillissements-Verordening, Staatsblad 217/1905 and Staatsblad 348/1906) so that the Government issued Government Regulation in Lieu of Law Number 1 of 1998 concerning Amendments to the Bankruptcy Law. In PERPPU 1/1998, it provides easy bankruptcy application requirements where the conditions only require 2 creditors and one of the creditors has a debt that has matured. Until Law No. 37/2004 on Bankruptcy and PKPU was enacted, the requirements for bankruptcy applications remained unchanged, so this paper aims to analyze the requirements for filing bankruptcy applications, which tend to be pro-creditor, so that it is straightforward to put debtors in a state of bankruptcy or PKPU, where the existence of the Bankruptcy and PKPU Law should provide help for debtors to find a solution to the debt pressure that has hit the debtor.